2013
DOI: 10.1177/1464420713499513
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element analysis of mechanical and fracture behavior of SiC particulate filled A356 alloy composites: Part I

Abstract: In the present study, silicon carbide (SiC) filled cast aluminum (A356) alloy composites were fabricated using stir casting technique by varying SiC weight percentages from 0 wt.% to 25 wt.% at a range of 5 wt.%, respectively. The spherical shaped SiC particles of 60 mm size were uniformly mixed with the semi-solid alloy by mechanical stirrer. The physical and mechanical properties along with the fracture toughness of SiC filled A356 alloy composite were evaluated experimentally and compared with finite elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Usually an idealised filler geometry is assumed such as circles and ellipsoids in 2D or spheres and spheroids in 3D [41], [42], [43], [44]. To investigate this assumption, an image based mesh generation algorithm was used [45] to generate a 2D mesh of the actual composite geometry by representing the TATB crystals as a set of polygons.…”
Section: Mesh Generationmentioning
confidence: 99%
“…Usually an idealised filler geometry is assumed such as circles and ellipsoids in 2D or spheres and spheroids in 3D [41], [42], [43], [44]. To investigate this assumption, an image based mesh generation algorithm was used [45] to generate a 2D mesh of the actual composite geometry by representing the TATB crystals as a set of polygons.…”
Section: Mesh Generationmentioning
confidence: 99%
“…The porosity increases as the weighting percentage of particles increases. In [21] it was found that the porosity content of the Al composites varied from 1.01% to 2.69% with the increased SiC wt % from 0% to 25%. A parametric study was performed, where a similar increase-relationship between the amount of porosity and the content of SiC particles is maintained; where the porosity increases as the volume fraction of reinforcement do.…”
Section: Porous Al-matrix and Pore-free Sic Particlementioning
confidence: 99%
“…However, in this study the porosity effect was not included in the numerical model, instead, it analyzed with the (R-A) analytical model. MMC porosity arises generally by causes of gas entrapment and the evolution of dissolved gases [21]. Although the porosity in MMC can be diminished, its existence is unavoidable [22].…”
Section: Introductionmentioning
confidence: 99%
“…w Al is the weight fraction of pure aluminum. This rule of mixture was used to calculate theoretical density, and actual density was calculated using the Archimedes principle [31].…”
Section: Physical and Mechanical Characterization 231 Void Contentmentioning
confidence: 99%